Low cycle fatigue life modelling using finite element strain range partitioning for a steam turbine rotor steel. (June 2020) - Azeez, Ahmed; Eriksson, Robert; Leidermark, Daniel; Calmunger, Mattias
Highlights: Steam turbine rotor steel FB2 under fully reversed isothermal low cycle fatigue. Finite element strain range partitioning of the inelastic strain amplitude. Fatigue life model based on plasticity- and creep-dominated damage. Creep damage at 600 °C in the form of voids close to the fracture surface. Fraction of low angle grain boundary using electron backscatter diffraction. Abstract: Materials made for modern steam power plants are required to withstand high temperatures and flexible operational schedule. Mainly to achieve high efficiency and longer components life. Nevertheless, materials under such conditions experience crack initiations and propagations. Thus, life prediction must be made using accurate fatigue models to allow flexible operation. In this study, fully reversed isothermal low cycle fatigue tests were performed on a turbine rotor steel called FB2. The tests were done under strain control with different total strain ranges and temperatures (20 ° C to 625 ° C). Some tests included dwell time to calibrate the short-time creep behaviour of the material. Different fatigue life models were evaluated based on total life approach. The stress-based fatigue life model was found unusable at 600 ° C, while the strain-based models in terms of total strain or inelastic strain amplitudes displayed inconsistent behaviour at 500 ° C. To construct better life prediction, the inelastic strain amplitudes were separated into plastic and creep components by modelling the deformation behaviour of the material, including creep. Based on strain range partitioning approach, the fatigue life depends on different damage mechanisms at different strain ranges at 500 ° C. This allows for the formulation of life curves based on either plasticity-dominated damage or creep-dominated damage. At 600 ° C, creep dominated while at 500 ° C creep only dominates for higher strain ranges. The deformation mechanisms at different temperatures and total strain ranges were characterised by scanning electron microscopy and by quantifying the amount of low angle grain boundaries. The quantification of low angle grain boundaries was done by electron backscatter diffraction. Microscopy revealed that specimens subjected to 600 ° C showed signs of creep damage in the form of voids close to the fracture surface. In addition, the amount of low angle grain boundaries seems to decrease with the increase in temperature even though the inelastic strain amplitude was increased. The study indicates that a significant amount of the inelastic strain comes from creep strain as opposed of being all plastic strain, which need to be taken into consideration when constructing a life prediction model.